COMPARISON OF EFFECTIVENESS OF ANTIPSYCHOTICS IN SCHIZOPHRENIA: SECOND-GENERATION VERSUS THE FIRST-GENERATION - Zubair, Usama Bin; Ali, Syed Azhar; Taj, Rizwan; Batool, Syeda Misbah (Journal of Ayub Medical College Abbottabad, 2020)
Background: The choice of the antipsychotic medication is based upon the risks, benefits and the cost. There has been still a debate that which group of antipsychotics is overall better amongst the two so we planned this study with the objective to compare the efficacy of the 1st & 2nd generation antipsychotics for the treatment of schizophrenia. Methods: This RCT was conducted at in/out patient department of Psychiatry at a tertiary care hospital of Pakistan over the time period of six months. All the patients of schizophrenia between 18-50 years of age of either gender and all the socioeconomic groups were included in the study. Each patient was assessed with the Simpson-Angus Scale (SAS) for the EPS and the Positive and Negative Syndrome Scale (PANSS) for the schizophrenia at the baseline, 6 weeks and 12 weeks after starting the designated medication. Results: The mean age of the 350 patients included in the study was 34.25±16.74 years. One hundred and forty-eight (42.3%) patients were female and 202 (57.7%) were male. The overall response of 1st Generation & 2nd Generation antipsychotics was 51 (140) 36% and 135 (210) 64% respectively (p-value=0.00024). Sixty-three (45%) patients who were taking 1st Generation Antipsychotics had relapse of the disease as compared to the 29 (13.7%) patients who were taking the 2nd Generation antipsychotics. Dryness of mouth, sedation and EPS were the common side effects with the 1st generation antipsychotics while dryness of mouth, cardiac arrhythmias, and sexual dysfunction were the common side effects with the 2nd generation antipsychotics. Conclusion: This study concluded that the 2nd generation antipsychotics were superior to the 1st generation antipsychotics among the patients of schizophrenia in terms of the success rate, relapse rate and the tolerability. Keywords: Effectiveness; Antipsychotics; Schizophrenia